Caracterização de diferentes frações derivadas do pinhão (Araucaria angustifolia) e suas aplicações para o desenvolvimento de produtos - Lauer, Alan (2019)
Currently, it is a growing search for the development of new products, both by the food and pharmaceutical industries, with the application of unconventional raw materials. There are regional products with great potential for use, not yet fully explored, such as the pine nut, Araucaria angustifolia seed. Driven by the valorization of the use of products with natural origin, without the use of pesticides and that present regionalization characteristics, that value the small producers and the sustainable extractivism, the present work aimed to study different ways of using the Araucaria’s pine for production of new products, increasing their consumption. Thus, two different production processes of pine nut flour (raw and cooked) were developed with the purpose of increasing the useful life of this raw material. From these flours was developed a fermented milk plus Lactobacillus acidophilus that presented good nutritional quality and acceptance with the consuming public (grade 7.68 in the hedonic evaluation). It was also developed a creamy cheese plus cooked pine nut flour with innovative characteristics, combining the benefits of cheese and pine nuts, which presented good acceptance (grade 2.60 - preference attribution test). Both products were considered strong candidates for industrial scale production, with commercialization as innovative products. As a proposal for the complete use of the raw material, the pinion bark, a waste product, was used to produce aqueous and hydroalcoholic extracts, which were lyophilized and used to evaluate their antimicrobial action, showing satisfactory results against Staphylococcus aureus strains. (aqueous-17.0I cm, hydroalcoholic-14.0R cm) proving to be a promising product as an antimicrobial phytotherapic. With this work it was possible to develop products with innovative and potential characteristics for countless future applications